High‐Throughput Separation of Microvesicles from Whole Blood Components Using Viscoelastic Fluid. Issue 12 (8th November 2020) - Nam, Jeonghun; Yoon, Jung; Jee, Hyunseul; Jang, Woong Sik; Lim, Chae Seung
Abstract: Cell‐derived microvesicles (MVs, also known as microparticles, MPs) are known as important biomarkers of various diseases including cardiovascular diseases, infectious diseases, and cancer. Development of techniques for blood cell removal and MV isolation is required for downstream analyses in biological and clinical applications. A sheathless, label‐free, viscoelastic microfluidic device is proposed for the separation of submicrometer platelet‐derived MPs (PDMPs) from whole blood. Flow rate and channel length dependent performance of the device is evaluated using 2‐µm particles as analogs to platelets and hematocrit (Hct) dependent flow characteristics of red blood cells (RBCs) are observed. In addition, the removal rate of nanoparticles of sizes 300, 500, 700, and 1000 nm is evaluated, and finally, the device is applied to examine the recovery of PDMPs from diluted whole blood sample. At Q = 200 µL min −1 in a 15‐mm long microchannel, RBCs at 5% Hct and platelets are removed to the central outlet without platelet activation, while PDMPs are successfully isolated to the side outlets within ≈2 min. The PDMPs collected from the device are analyzed by flow cytometry. The device exhibits ≈4.8‐fold enhanced isolation performance compared to the centrifugation method. Abstract : Development of techniques for blood cell removal and microvesicle (MV) isolation is required for downstream analyses in biological and clinical applications. A sheathless, label‐free, viscoelastic microfluidic device is proposed for the separation of submicrometer MVs from whole blood. This device enables the isolation of platelet‐derived microparticles (PDMPs) from diluted whole blood sample within ≈2 min without platelet activation.